RANCANG BANGUN ALAT PEMANTAU LAJU DETAK JANTUNG SAAT LATIHAN FISIK - Harsono, Budi; Liman, Johansah; Djohan, Nani (Teknik dan Ilmu Komputer, 2012)
Knowing heart rates while doing physical exercises is very useful to achieve maximum exercise results. The use of manual method to measure heart rates during physical exercises is not possible; therefore a tool to monitor the heart rate continuously while doing a physical exercise is needed. This research aimed at designing a heart rate monitor to be used during the physical exercise.Â The heart rate monitoring was done with reflective photoplethysmography method using a pair of white LED sensor and photodiode. The heart rate monitor made was compared with other heart rate monitor products using photoplethysmography technique. The test results showed that the tool can be used during the physical exercise having a better response rate than the similar products tested.Â Keywords: heart rate, heart rate monitoring, photoplethysmography, exercise